Bilateral agreement for the academic years 2008-2009, 2012-2013 LLP Programme between programme: higher education (Erasmus) between Università Iuav di Venezia and Universidade Lusíada de Lisboa - Universidade Lusíada de Lisboa (2016)
- Cooperate for exchange of students and/or staff in the context of the Erasmus programme. - Subject area: Art and design.